2021
DOI: 10.1177/26350106211051298
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the School Day on Health Behaviors for Children With Type 1 Diabetes: A Survey of Parent Perspectives During the COVID-19 Pandemic

Abstract: Purpose The purpose of this study is to survey parents of youth with type 1 diabetes during the COVID-19 pandemic with school closures to better understand the implications of the school day on health care behaviors. Methods A cross-sectional, online survey was distributed to parents of youth with type 1 diabetes ≤19 years of age in a large, academic diabetes center. Questions encompassed perceived changes in management behaviors and plans for return to school. Subgroup analysis compared parent responses by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…Although parents overwhelmingly reported that management of their child’s T1DM was easier during the COVID-19 pandemic, reduced physical activity and increased sedentary time were consistently described as key diabetes management challenges. This is consistent with an accumulating body of evidence in children, young adults, and adults with diabetes highlighting reductions in physical activity 6 , 9 - 11 , 20 , 22 - 25 , 31 and increases in screen time 11 , 31 during the COVID-19 pandemic. Given that health risks associated with excess screen time include poor sleep, insulin resistance, and cardiovascular disease, 32 marked increases in screen time during the pandemic are particularly concerning for children with T1DM, who are at a higher risk of cardiovascular disease compared to those without diabetes.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Although parents overwhelmingly reported that management of their child’s T1DM was easier during the COVID-19 pandemic, reduced physical activity and increased sedentary time were consistently described as key diabetes management challenges. This is consistent with an accumulating body of evidence in children, young adults, and adults with diabetes highlighting reductions in physical activity 6 , 9 - 11 , 20 , 22 - 25 , 31 and increases in screen time 11 , 31 during the COVID-19 pandemic. Given that health risks associated with excess screen time include poor sleep, insulin resistance, and cardiovascular disease, 32 marked increases in screen time during the pandemic are particularly concerning for children with T1DM, who are at a higher risk of cardiovascular disease compared to those without diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…These perceived improvements in glycemic control are consistent with findings of recent studies conducted among children and adults with T1DM during the COVID-19 pandemic in other countries, 19 such as Italy, 8 - 10 , 19 , 20 , Spain, 19 the United Kingdom, 19 and Malaysia. 11 However, literature remains mixed 19 because several other studies, including those conducted in the United States, 6 , 21 Saudi Arabia, 22 Japan, 23 India, 24 and Italy, 25 reported either poorer glycemic control or no significant change during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations